The Star of Kazan - Ibbotson, Eva (Puffin Books, 2006)
After twelve-year-old Annika, a foundling living in late-nineteenth-century Vienna, inherits a trunk of costume jewelry, a woman claiming to be her aristocratic mother arrives and takes her to live in a strangely decrepit mansion in Germany.